Fuzzy Adaptive Controller Design for IPMSM with System Uncertainties and Disturbances Considering - Vu, Nga Thi-Thuy (Old Journal, 2020)
This paper proposed a T-S fuzzy model based adaptive fuzzy controller for the interior permanent magnet synchronous motors. Firstly, the T-S fuzzy model of the system is built based on the nonlinear dynamic model. Next, the adaptive fuzzy controller is designed to deal with the problems of system uncertainties and external disturbances. This controller includes two phases, one is for system stability and one for compensating the effect of the unknown components. The stability of the system, as well as the convergence of the adaptive law, is mathematically proven through Lyapunov theory. Finally, some simulations are done to verify the effectiveness of the presented scheme. The simulation results show that the proposed algorithm has a good response to the change of reference input, the system parameters variation, and the sudden change of the load torque.